Phosphate ages in Apollo 14 breccias: Resolving multiple impact events with high precision U–Pb SIMS analyses. (1st February 2016) - Snape, J.F.; Nemchin, A.A.; Grange, M.L.; Bellucci, J.J.; Thiessen, F.; Whitehouse, M.J.
Abstract: The U–Pb systems of apatite and merrillite grains within four separate Apollo 14 impact melt breccia samples were analysed by secondary ion mass spectrometry. No systematic difference was identified between the 207 Pb/ 206 Pb ages of the apatites and merrillites. A combined 207 Pb/ 206 Pb age of 3927 ± 2 Ma (95% conf.) is determined for three of these samples (14305, 103: 3926 ± 4 Ma; 14306, 150: 3926 ± 6 Ma; 14314, 13: 3929 ± 4 Ma). By combining these data with the ages previously obtained for zircons in Apollo 12 impact melt breccia fragments and the lunar meteorite SaU 169, a weighted average age of 3926 ± 2 Ma (95% conf.) is obtained, which is attributed to the formation of the Imbrium basin. An age of 3943 ± 5 Ma is determined for the fourth breccia (14321, 134), which is similar to ages of 3946 ± 15 Ma and 3958 ± 19 Ma, obtained from several older phosphates in 14305, 103 and 14314, 13. The weighted average of these three older ages is 3944 ± 4 Ma (95% conf.). This is indistinguishable to the age (3938 ± 4 Ma; 2 σ ) obtained for a different Apollo 14 impact melt breccia in a previous study. After investigating likely sources for this older ∼3940 Ma age, we conclude that the Humorum or Serenitatis basin forming events are likely candidates. The potential identification of two large impact events within ∼15 Myrs has important implications for the rate of lunar bombardment around 3.95–3.92 Ga. This study demonstrates the importance of high-precision age determinations for interpreting the impact record of the Moon, as documented in lunar samples.